Viscous Magnetization and Ferromagnetic Composition of Stony Meteorites and Lunar Materials - Nagata, Takesi (1980)
P(論文) Effects of the shock metamorphism on stony meteorites are compared with those on lunar materials with respect to (a) the viscous magnetization which represents a relative abundance of superparamagnetically fine metallic grains produced by the explosive shock metamorphism and (b) the magnetic phase composition of metallic nickel-irons which represents effects of their remelting (or reheating up to about 1000℃) followed by rapid cooling caused by the shock metamorphism. Experimental results show that the Type (II) viscous magnetization, which gives the presence of superparamagnetic metallic grains more than 1/4 of total metal, is observed in almost all lunar fines and breccias but none of stony meteorites possesses the Type (II) viscous magnetization, and that almost all stony meteorites are still maintaining a magnetic phase composition resulted from a slow cooling of a metallic melt, approximately keeping the phase equilibrium condition, whereas the majority of lunar materials, particularly lunar breccias, contain the secondary products of a remelting (or a reheating) followed by a rapid cooling such as α_2-phase of metallic nickel-iron, schereibersite, and pure metallic iron exsolved from Fe-bearing silicate minerals by the subsolidus reduction process. These experimental results may lead to a conclusion that the lunar surface materials were seriously shock metamorphased probably owing to repeated meteorite impacts, whereas most stony meteorites have been subjected to much less shock effects than in the case of lunar materials. departmental bulletin paper